ChemInform Abstract: A High‐Pressure Route to Thermoelectrics with Low Thermal Conductivity: The Solid Solution Series AgInxSb1‐xTe2 (x = 0.1—0.6). Issue 44 (14th October 2013) - Schroeder, Thorsten; Rosenthal, Tobias; Souchay, Daniel; Petermayer, Christian; Grott, Sebastian; Scheidt, Ernst‐Wilhelm; Gold, Christian; Scherer, Wolfgang; Oeckler, Oliver
Abstract Title compounds with x = 0.1, 0.2, 0.4, 0.5 and 0.6 are prepared by solid state reaction of stoichiometric mixtures of the elements (sealed silica ampoules, 950 °C, Ar) followed by hot isostatic pressing (multianvil press, 2.5 GPa, 400 °C, 5 h).